2012
DOI: 10.1002/poc.1958
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐site exchange in intramolecular complexes of silicon: substituent effects

Abstract: The intramolecular complexes containing coordination bonds Si←N or Si←O are distinguished for their stereochemical nonrigidity resulting in interconversion between isomers, that is, ligand‐site exchange. The influence of the substituents bound to the silicon atom on the free energies of activation for ligand exchange ΔG≠ of specific interest is poorly understood. In this work, the literature data on substituent influence on the energies ΔG≠ for 13 series of the complexes have been considered, using the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…In summary, we will point out that the polarizability effect influences significantly a great variety of physical properties of individual compounds and the complexes thereof, the BDEs in organometallic systems among them. There is good reason to believe that this effect influences the chemical properties of organometallic compounds.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In summary, we will point out that the polarizability effect influences significantly a great variety of physical properties of individual compounds and the complexes thereof, the BDEs in organometallic systems among them. There is good reason to believe that this effect influences the chemical properties of organometallic compounds.…”
Section: Resultsmentioning
confidence: 96%
“…Over a period of years, we investigate intensively the influence of polarizability effect on a great variety of physical properties such as the ionization potentials, electron affinities, core‐electron binding energies, spectroscopic and thermodynamical characteristics of H‐complexes, transition metal complexes, and radical ions . The polarizability effect consists in an electrostatic attraction between the excess charge q originating on the reaction (indicator) center R C and the dipole moment induced by this charge in the substituents X.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first evidence for this effect has come from the study of ionic gas-phase reactions involving simple organic molecules [28e30]. Further investigations demonstrated that the polarizability effect has a profound influence on the parameters of the IR [31], NMR [32,33], EPR [34], NQR [35], UVeVis electronic [36], ultraviolet photoelectron [37,38], X-ray photoelectron [39], and Mossbauer [40] spectra as well as on the bond lengths [41] and toxicity [42] of organometallic compounds. A necessary condition for arising this effect is initiation of the partial charge q on M atom and/or on bonds MÀB and MÀL.…”
Section: Introductionmentioning
confidence: 99%